An update on new antibiotic prophylaxis and treatment for urinary tract infections in children. (13th October 2017) - Delbet, Jean Daniel; Lorrot, Mathie; Ulinski, Tim
ABSTRACT: Introduction : This review focuses on the treatment of urinary tract infections (UTI) in children and in particular its recent changes. Areas covered : Acute pyelonephritis, acute cystitis and asymptomatic bacteriuria or asymptomatic infections have to be clearly distinguished. Prompt treatment is required in pyelonephritis and cystitis, but not in asymptomatic bacteriuria or infection, in order to avoid selection of more virulent strains. This concept should be considered even in immunocompromised or bedridden children. In case of pyelonephritis, there should be no delay in beginning the antibiotic treatment in order to decrease the risk of long term complication, such as renal scars. Predisposing conditions for UTI, such as voiding anomalies and urinary tract malformation should be carefully evaluated. Expert opinion : One major concern is the increasing resistance to 3 rd generation cephalosporins. Therefore overconsumption in low-risk settings should be absolutely avoided. The prevalence of infections with E. coli producing extended spectrum ß-lactamase (ESBL) is increasing and pediatricians should be aware about the specific treatment options. Any recommendation about (initial) antibiotic treatment should be regularly updated and adapted to local resistance profiles and to economic factors in different health systems.